The global burden of high BMI among adolescents between 1990 and 2021 - Chenliang Ge; Jingwei Xiong; Rui Zhu; Zhenchen Hong; Yan He (Communications Medicine)
Abstract Background Adolescent high body mass index (BMI) is a growing global health problem. This study analyzes global, regional, and national prevalence and trends of high BMI among adolescents (aged 10–19 years) from 1990 to 2021, investigates disparities by sex, country, and socio-demographic index (SDI), and projects prevalence to 2030. Methods This study analyzed Global Burden of Disease (GBD) study 2021 data. Prevalence and trends of high BMI among adolescents were stratified by sex, SDI, and region. Estimated annual percentage change (EAPC), joinpoint regression, and Bayesian age-period-cohort (BAPC) analysis were used to quantify trends and project prevalence to 2030. Results Global adolescent high BMI prevalence has increased from 8.36% (1990) to 17.64% (2021), with females having a slightly higher prevalence than males. Marked disparities are observed across SDI levels; high SDI countries have the highest prevalence, but middle SDI countries are experiencing the fastest increases. Substantial geographic variations are also evident, with particularly rapid increases in some regions, such as the Pacific Island nations, and slower growth or declines in others, such as parts of East Asia. The BAPC model projects a continued rise in global high BMI prevalence up to 2030, with considerable variation across individual countries. Conclusions The global rise of high BMI among adolescents, coupled with projections of continued increases, presents a pressing public health concern. The observed disparities across SDI levels and geographic regions necessitate tailored interventions to address this growing epidemic effectively.